Risk predictors for the development of retinopathy of prematurity in very low birth weight neonates - Shreetal, Sheena; Sobhakumar, S; Rhiju, Reshmi; Nair, Shreetal Rajan (Indian Journal of Child Health, 2016)
Background: Retinopathy of prematurity (ROP) is an important cause of visual and neurological impairment in premature infants. Identification of risk factors and effective management of the same will help in better outcomes. Information on ROP and its risk factors are limited especially from South India and interventions directed at prevention and treatments have produced only modest results. Methods: The study was of a prospective, unmatched case–control design and was conducted in premature, very low birth weight infants (